SEED CAROTENOID DEFICIENT Functions in Isoprenoid Biosynthesis via the Plastid MEP Pathway. Issue 4 (4th February 2019) - Zhang, Lili; Zhang, Xuan; Wang, Xiaoji; Xu, Jing; Wang, Min; Li, Lin; Bai, Guanghong; Fang, Hui; Hu, Shuting; Li, Jigang; Yan, Jianbing; Li, Jiansheng; et al.
Abstract : SEED CAROTENOID DEFICIENT functions in the methylerythritol phosphate pathway in maize and affects the accumulation of downstream isoprenoids. Abstract: Plastid isoprenoids, a diverse group of compounds that includes carotenoids, chlorophylls, tocopherols, and multiple hormones, are essential for plant growth and development. Here, we identified and characterized SEED CAROTENOID DEFICIENT ( SCD ), which encodes an enzyme that functions in the biosynthesis of plastid isoprenoids in maize ( Zea mays ). SCD converts 2 C -methyl-d -erytrithol 2, 4-cyclodiphosphate to 1-hydroxy-2-methyl-2-(E)-butenyl 4-diphosphate in the penultimate step of the methylerythritol phosphate (MEP) pathway. In scd mutants, plant growth and development are impaired and the levels of MEP-derived isoprenoids, such as carotenoids, chlorophylls, and tocopherols, as well as abscisic and gibberellic acids, are reduced in leaves and seeds. This scd metabolic alteration varies among plant tissues and under different light conditions. RNA-sequencing of the scd mutant and wild type identified a limited number of differentially expressed genes in the MEP pathway, although isoprenoid levels were significantly reduced in scd seeds and dark-grown leaves. Furthermore, SCD -overexpressing transgenic lines showed little or no differences in isoprenoid levels, indicating that SCD may be subject to posttranslational regulation or not represent a rate-limiting step in the MEP pathway. These results enhance our understanding of the transcriptomic and metabolic regulatory roles of enzymes in the MEP pathway and of their effects on downstream isoprenoid pathways in various plant tissues and under different light conditions.